Redefining C and D in the Petunia ABC - Heijmans, Klaas (American Society of Plant Biologists, 2012)
According to the ABC(DE) model for flower development, C-genes are required for stamen and carpel development and floral determinacy, and D-genes were proposed to play a unique role in ovule development. Both C- and D-genes belong to the AGAMOUS (AG) subfamily of MADS box transcription factors. We show that the petunia (Petunia hybrida) C-clade genes PETUNIA MADS BOX GENE3 and FLORAL BINDING PROTEIN6 (FBP6) largely overlap in function, both in floral organ identity specification and floral determinacy, unlike the pronounced subfunctionalization observed in Arabidopsis thaliana and snapdragon (Antirrhinum majus). Some specialization has also evolved, since FBP6 plays a unique role in the development of the style and stigma. Furthermore, we show that the D-genes FBP7 and FBP11 are not essential to confer ovule identity. Instead, this function is redundantly shared among all AG members. In turn, the D-genes also participate in floral determinacy. Gain-of-function analyses suggest the presence of a posttranscriptional C-repression mechanism in petunia, most likely not existing in Arabidopsis. Finally, we show that expression maintenance of the paleoAPETALA3-type B-gene TOMATO MADS BOX GENE6 depends on the activity of C-genes. Taken together, this demonstrates considerable variation in the molecular control of floral development between eudicot species.